2023
DOI: 10.1002/aoc.7042
|View full text |Cite
|
Sign up to set email alerts
|

A novel azo‐azomethine benzoxazole‐based ligand and its transition metal (II), (III), (IV) complexes: Synthesis, characterization, theoretical studies, biological evaluation, and catalytic application

Abstract: This work describes the synthesis of a novel multiple dentation azo-Schiff base dye 2- ((3-((5-chlorobenzo[d]oxazol-2-yl)diazenyl)-4-hydroxybenzylidene) amino)pyridin-3-ol (H 2 L) based mixed heterocyclic bnzoxazole and pyridine moieties in facile two successive steps approach. Firstly is the synthesis of start azo dye 3- ((5-chlorobenzo[d]oxazol-2-yl)diazenyl)-4-hydroxybenzaldehyde (CBOAHB) followed by condensation with 3-hydroxy 2-amino pyridine. It's novel binuclear Ni (II), Cu (II), Ru (III), and Zr (IV) 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 83 publications
(122 reference statements)
0
7
0
Order By: Relevance
“…Moreover, the spectra of the free ligand exhibit additional spectral bands at (3126 and 3046) cm −1 and (3120 and 2924) cm −1 correspond to υ(C‐H armatic ) and υ(C‐H aliphatic ) for (DMPDE) and Ag(I) complex respectively. The appearance of stretching vibration is characterized by υ(C−H), It is confirmed that the ligand conforms to an azo structure does not form a hydrazo structure and reacts with metal ions through the azo moiety [52] . Triplet bands were also noticed at (1674, 1599, 1491) and (1675, 1601, 1495) cm −1 for DMPDE and Ag(I) complex were related to υ(C=O), υ(C=N) and υ(N=N).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, the spectra of the free ligand exhibit additional spectral bands at (3126 and 3046) cm −1 and (3120 and 2924) cm −1 correspond to υ(C‐H armatic ) and υ(C‐H aliphatic ) for (DMPDE) and Ag(I) complex respectively. The appearance of stretching vibration is characterized by υ(C−H), It is confirmed that the ligand conforms to an azo structure does not form a hydrazo structure and reacts with metal ions through the azo moiety [52] . Triplet bands were also noticed at (1674, 1599, 1491) and (1675, 1601, 1495) cm −1 for DMPDE and Ag(I) complex were related to υ(C=O), υ(C=N) and υ(N=N).…”
Section: Resultsmentioning
confidence: 82%
“…The appearance of stretching vibration is characterized by υ(CÀ H), It is confirmed that the ligand conforms to an azo structure does not form a hydrazo structure and reacts with metal ions through the azo moiety. [52] Triplet bands were also noticed at (1674, 1599, 1491) and (1675, 1601, 1495) cm À 1 for DMPDE and Ag(I) complex were related to υ(C=O), υ(C=N) and υ(N=N). In the spectrum of the azo ligand, there are two feature moiety pairs: υ(N=N) and υ(À CÀ N=NÀ CÀ ).…”
Section: Ftir Spectramentioning
confidence: 89%
“…In the case of the CrAz 2 complex, the electronic spectrum band at 615 nm was connected to the transition of 4 A 2g (F) → 4 T 2g (F) in the octahedral geometry complex. 52 The 3.84 B.M magnetic moment found for the CrAz 2 complex may be described by the occurrence of a d 3 (t 2g…”
Section: Magnetic Moment and Electronicmentioning
confidence: 95%
“…Research in the fields of biology, electrochemistry, and analysis may all make use of these substances in a variety of different ways . Because of their potential cytotoxicity as well as their antibacterial, antifungal, and antioxidant capabilities, they have garnered a lot of studies. , There has been a significant amount of research done on the production of metal­(II) complexes of azo compounds, as well as their biological activity. , Because their azo group possesses powerful medicinal properties, azo dyes are advantageous chelating agents for a variety of metal ions, , due to the azo group of these dyes. In addition to this, it has been demonstrated that azo metal complexes can be beneficial as metal anticorrosion agents and as thermally stable optical storage devices, , …”
Section: Introductionmentioning
confidence: 99%
“…12–14 Copper-based complexes acting as alternatives to expensive metals, have been employed in the degradation of dyes, and exhibit superior reactivity. 15–17 However, there are several disadvantages to homogenous catalysts that prevent their application, such as the inability to achieve easy separation and high recyclability of these catalysts. To overcome these drawbacks, heterogenization of catalysts has occurred in the last few years.…”
Section: Introductionmentioning
confidence: 99%